2002
DOI: 10.1063/1.1461903
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-related local vibrational modes in ZnO:N

Abstract: We study the influence of nitrogen, a potential acceptor in ZnO, on the lattice dynamics of ZnO. A series of samples grown by chemical vapor deposition ͑CVD͒ containing different nitrogen concentrations, as determined by secondary ion mass spectroscopy ͑SIMS͒, was investigated. The Raman spectra revealed vibrational modes at 275, 510, 582, 643, and 856 cm Ϫ1 in addition to the host phonons of ZnO. The intensity of these additional modes correlates linearly with the nitrogen concentration and can be used as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
249
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 454 publications
(271 citation statements)
references
References 18 publications
22
249
0
Order By: Relevance
“…The band at 241 cm -1 is not readily identified, but we note that there is a peak in the calculated phonon density of states for ZnO at this wavenumber [45] although it appears that this is not normally observed. Indeed, there is no occurrence of a Raman peak at precisely this wavenumber in an extensive catalogue of (transition and other) metal compounds [46] but it is interesting to note that a strong peak has been observed at 240 cm -1 in nanophase TiO 2 [47] which was not clearly identified but was attributed to a long range order effect, occurring when bands known to be characteristic of the crystal structure were strong.…”
Section: Accepted M Manuscriptmentioning
confidence: 89%
“…The band at 241 cm -1 is not readily identified, but we note that there is a peak in the calculated phonon density of states for ZnO at this wavenumber [45] although it appears that this is not normally observed. Indeed, there is no occurrence of a Raman peak at precisely this wavenumber in an extensive catalogue of (transition and other) metal compounds [46] but it is interesting to note that a strong peak has been observed at 240 cm -1 in nanophase TiO 2 [47] which was not clearly identified but was attributed to a long range order effect, occurring when bands known to be characteristic of the crystal structure were strong.…”
Section: Accepted M Manuscriptmentioning
confidence: 89%
“…As the intensity of those peaks increased linearly with N concentration, it was further suggested that their intensity could be used to determine the N concentration in N-doped ZnO samples. 5 However, Bundesmann et al disputed this interpretation, as they detected similar peaks in ZnO thin films doped with Fe, Sb, and Al, intentionally grown without N incorporation. 6 They attributed the additional Raman peaks to intrinsic host lattice defects.…”
mentioning
confidence: 92%
“…3 Being nitrogen the primary acceptor candidate in ZnO, considerable effort has been devoted to characterize, by means of vibrational spectroscopy, the impurity incorporation and the formation of complexes that may reduce the doping efficiency of N in ZnO. [4][5][6][7] Kaschner et al 5 reported the observation of several additional Raman peaks between 275 and 643 cm −1 in N-doped GaN epitaxial films grown by chemical vapor deposition. They were attributed to local vibrational modes ͑LVMs͒ of N in substitutional O site in the ZnO lattice.…”
mentioning
confidence: 99%
“…Chen et al reported that this broad peak in the O + -implanted ZnO single crystal was much smaller than that in the B + -implanted one [21]. This broad Raman peak at around 580 cm −1 has been attributed to oxygen deficiency in ZnO [21][22][23]. The increase of the broad Raman peak indicates that VO was formed by the Zn-annealing.…”
Section: Resultsmentioning
confidence: 93%